Child-friendly school in improving children's confident character - Dwi Wahyu Ro'is Saputri; Rachma Hasibuan (Atfaluna: Journal of Islamic Early Childhood Education, 2022)
This study aims to evaluate the effectiveness of a child-friendly school (CFS) in improving children's self-esteem. In addition, it also describes the implementation of child-friendly schools in learning activities, facilities and infrastructure The study applied descriptive qualitative approach. The informants were the principal, teacher, and students aged 4-5 at Pembina Srengat State Kindergarten. The researcher gathered data through interviews, documentation, and observation. The result of this study suggest that CFS adoption has a considerable impact on boosting self-confidence. Children can express their emotions during play and learning activities, share their thoughts, and carry out the many duties assigned by the teacher. Although the teacher occasionally gives the students additional direction due to the children's frequently clashing personalities in early childhood, the character of self-confidence has been accomplished. It follows that creative and engaging teachers can influence students' feelings of enjoyment while studying, thereby continually developing a self-assured character.